Knowledge Based Approach in Differential Diagnosis of Intracranial Cysts -A Requisite to Avoid Unwarranted Interventions - Verma, A; Moiyadi, A; Arya, S; Jalali, R; Menon, H; Karbhase, G; Sahwale, P (Nepalese Journal of Radiology, 2012)
Neuroglial cyst is a rare abnormality that is usually asymptomatic and an incidental detection in imaging done for an unrelated cause. An emphasis on this message is the prime aim of the present report. We came across a patient being treated for chronic myeloid leukemia having vague neurological symptoms for which Magnetic Resonance Imaging (MRI) was done. No detectable cause explaining his symptomatology was noted on imaging. A cystic lesion was however noted in right frontal lobe which was labeled as a neuroglial cyst. No treatment was mandated as per discussion in the neuro-oncology working group of our centre. Follow up was advised to confirm the impression as an attempt to achieve a histological diagnosis would have been ethically not justified. The patient reported regularly for his chemotherapy regimen to the respective unit and was asymptomatic for the lesion till last follow up at six months. NJR I VOL 2 I ISSUE 1 35-38 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6978